Expanding the clinicopathological-genetic spectrum of glycogen storage disease type IXd by a Chinese neuromuscular center - Huang, Kun; Duan, Hui-Qian; Li, Qiu-Xiang; Luo, Yue-Bei; Bi, Fang-Fang; Yang, Huan (Frontiers in Neurology, 2022)
Background: Glycogen storage disease (GSDs) is characterized by abnormally inherited glycogen metabolism. GSD IXd, which is caused by mutations in the PHKA1 gene, is an X-linked rare disease with mild myopathic symptoms. To date, only 13 patients with GSD IXd have been reported. In this study, we aimed to expand the clinicopathological-genetic spectrum of GSD IXd at a neuromuscular center in China. Methods: Data on patients diagnosed with GSD IXd at our neuromuscular center were collected retrospectively. Clinical features, electrophysiology, muscle pathology, and genetic information were analyzed. Results: Between 2015 and 2021, three patients were diagnosed with GSD IXd based on clinical manifestations, pathological findings, and genetic testing. One patient presented with mitochondrial myopathy. All patients exhibited muscle weakness and elevated levels of creatine kinase. Electromyography-detected myopathic changes were found in two patients, whereas one patient refused to undergo this examination. Pathological examinations in all patients revealed subsarcolemmal accumulation of glycogen under PAS staining. All patients had mutations in the PHKA1 gene and the patient with mitochondrial myopathy also had a mutation in the MT-TL1 gene. Conclusion: Our study expands the clinicogenotype and phenotype of GSD IXd in a Chinese population. Our study also expands the known mutation spectrum for GSD IXd, contributing to a better characterization and understanding of this ultrarare neuromuscular disorder.